Factors that Influence the Implementation of Early Initiation of Breastfeeding in RSUP Haji Adam Malik Medan - Ali Imron; Ida Yustina; Etti Sudaryati (Berita Kedokteran Masyarakat (BKM), 2020)
Early Initiation of Breastfeeding (EIB) is placing the baby in the mother's stomach immediately after birth in a position of skin contact with the mother in an hour after birth, if there is no medical indication. RSUP Haji Adam Malik Medan was one of the government hospitals, education, national referrals, and plenary status had implementing EIB. Achievement of EIB in this hospital decreased from (27.71%) in 2016 to (23.08%) in 2017. The purpose of this study was to explore the implementation of EIB in RSUP Haji Adam Malik Medan. This was a qualitative research with a phenomenological approach through in-depth interviews. The informants were 6 people, consisting of 2 midwives and 1 structural official in medical services, 2 patients and 1 gynecologist. Implementation of EIB in the hospital wasn’t going well, the factors that influence EIB were communication, disposition and management’s function. The successful implementation of EIB can reduce maternal and infant mortality rates, suggested to RSUP Haji Adam Malik Medan forms a special team to monitoring and evaluates the implementation of EIB, set and carry out sanctions for implementation of EIB, and increases the competence and motivation of health workers.